2015
DOI: 10.1002/cssc.201500131
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐ and Vanadium‐Catalyzed Oxidative Cleavage of Lignin using Dioxygen

Abstract: Transition-metal-containing hydrotalcites (HTc) and V(acac)3 /Cu(NO3 )2 ⋅3 H2 O (acac=acetylacetonate) mixtures were tested for their catalytic activity in the cleavage of the lignin model compound erythro-1-(3,4-dimethoxyphenyl)-2-(2-methoxyphenoxy)-l,3-propanediol (1) with molecular oxygen as oxidant. Both catalytic systems displayed high activity and good selectivity and afforded veratric acid as the main product. The catalyst behavior was studied by EPR spectroscopy, XRD, and Raman spectroscopy. After the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 99 publications
2
99
0
2
Order By: Relevance
“…Va nadium-and copper-doped hydrotalcite materials were also found to depolymerise lignin under oxidative conditions, [347] whereby the hydrotalcite is believed to act as ar eservoir for the release of homogeneous copper and vanadium species.C atalysts doped both with vanadium and copper gave rise to synergistic properties,and the depolymerisation of an Organosolv lignin (extracted from Beech using mild water/ethanol conditions) led to as ignificant reduction in the apparent molecular weight (from 1100 to 300 Da, based on GPC analysis) in pyridine as solvent, under a1 .0 MPa pressure of O 2 .H SQC NMR spectra revealed the full conversion of b-ether and resinol structures and p-hydroxycinnamyl alcohols.T he low molecular weight fraction was assumed to consist of dimers or trimers,w hich was further supported by analysis by MALDI-TOF-MS,b ut these were not further isolated or identified. Ther eaction was also performed on Kraft lignin, for which degradation of the bether units was also observed.…”
Section: (Dtbby)][pfmentioning
confidence: 99%
“…Va nadium-and copper-doped hydrotalcite materials were also found to depolymerise lignin under oxidative conditions, [347] whereby the hydrotalcite is believed to act as ar eservoir for the release of homogeneous copper and vanadium species.C atalysts doped both with vanadium and copper gave rise to synergistic properties,and the depolymerisation of an Organosolv lignin (extracted from Beech using mild water/ethanol conditions) led to as ignificant reduction in the apparent molecular weight (from 1100 to 300 Da, based on GPC analysis) in pyridine as solvent, under a1 .0 MPa pressure of O 2 .H SQC NMR spectra revealed the full conversion of b-ether and resinol structures and p-hydroxycinnamyl alcohols.T he low molecular weight fraction was assumed to consist of dimers or trimers,w hich was further supported by analysis by MALDI-TOF-MS,b ut these were not further isolated or identified. Ther eaction was also performed on Kraft lignin, for which degradation of the bether units was also observed.…”
Section: (Dtbby)][pfmentioning
confidence: 99%
“…Bolm et al 221 also reported on the utilization of different transition-metal-containing HT materials for the oxidative cleavage of a lignin model compound, erythro-1-(3,5-dimethoxyphenyl)-2-(2-methoxyphenoxy)-1,3-propanediol, using molecular oxygen. Between the different transition metals studied (Co, Zn, Fe, Cu and V), the combination of Cu and V in the same HTC structure (a HT-Cu-V catalyst obtained by the intercalation of HT-Cu material with vanadate species) was very efficient in cleaving the β-O-4 linkage of the lignin model molecule, using either toluene or pyridine as solvents (conversion >99%).…”
Section: Lignin Depolymerizationmentioning
confidence: 99%
“…Oxidative cleavage of a dilignol model compound, erythro-1-(3,4-dimethoxyphenyl)-2-(2-methoxyphenoxy)-l,3-propanediol, was investigated employing transition metal containing hydrotalcite, and V(acac) 3 and Cu(NO 3 ) 2 .3H 2 O mixtures, with molecular oxygen as the oxidant [91]. Oxidative depolymerization of the dilignol model was influenced by the solvent selection, with negligible conversion observed in toluene, but good activity obtained in pyridine resulting in veratric acid as the major product.…”
Section: Oxidative Transformationsmentioning
confidence: 99%